Companion of Ostrowski Inequality for Multiplicatively Convex Functions - Badreddine Meftah; Abdelghani Lakhdari; Saleh Wedad; Chemeseddine djaber Benchettah (Sahand Communications in Mathematical Analysis)
The objective of this paper is to examine integral inequalities related to multiplicatively differentiable functions. Initially, we establish a novel identity using the two-point Newton-Cotes formula for multiplicatively differentiable functions. Using this identity, we derive Companion of Ostrowski's inequalities for multiplicatively differentiable convex mappings. The work also provides the results' applications.